ANALYSIS OF NON-PERFORMING FINANCING IN MEDIATING THE INFLUENCE OF INCOME DIVERSIFICATION, INFLATION, GROSS DOMESTIC PRODUCT, AND SIZE OF THE BANK ON STABILITY - Muammar Taufiqi Lutfi Mustofa; Abdul Aziz Nugraha Pratama; Pandu Nur Wicaksono; Yunior Pasagi; Puspa Rini (SEAN Institute, 2023)
The purpose of this research is to see the effect of income diversification, inflation, gross domestic product, and bank size on stability with using Non-Performing financing as a mediating variable at the Bank General Sharia in Indonesia. The type of research is descriptive qualitative with the regression model is panel data. This research uses secondary data obtained from the financial reports of Sharia Commercial Banks for the 2012-2021 period. Data processing uses E-Views software with purposive techniques sampling. From the results of the tests carried out it shows that diversification income (DP) has a significant positive effect on stability and inflation positive and insignificant effect on stability, gross domestic product (GDP) has a positive and insignificant effect on stability and bank size significant negative effect on stability, Non-Performing financing (NPF) has a significant negative effect on stability. Non-Performing financing (NPF) is able to mediate the effect of inflation on stability. Non-Performing financing (NPF) is unable to mediate the influence of income Diversification, Gross Domestic Product, dan Size of The Bank terhadap Stability.